1970
DOI: 10.21009/pbe.2-1.9
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Sumber Pengetahuan Tradisional Tanaman Obat yang Digunakan oleh Masyarakat Suku Dayak Desa

Abstract: Indonesia memiliki keanekaragaman hayati yang tinggi, terutama tumbuhan salah satunya di wilayah Kalimantan Barat. Masyarakat Kalimantan Barat masih sering memanfaatkan keanekaragaman tumbuhan tersebut dalam bidang kesehatan, salah satunya masyarakat suku Dayak Desa. Suku Dayak Desa sebagai salah satu suku yang mendiami wilayah di Kalimantan Barat masih mempertahankan tradisi pengobatan secara tradisional dengan memanfaatkan tumbuhan sebagai bahan obat-obatan.Tradisi tersebut menjadi suatu kearifan lokal pada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
1
13
0
3
Order By: Relevance
“…This source of knowledge is obtained from people's experiences both written and unwritten in utilizing plants as traditional medicines from generation to generation. This research is in line with the results of a study conducted by Merdekawati (2016) and Julung et al, (2018). They reported that knowledge and the use of traditional medicines were obtained from personal experience, experiments and carried out from generation to generation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This source of knowledge is obtained from people's experiences both written and unwritten in utilizing plants as traditional medicines from generation to generation. This research is in line with the results of a study conducted by Merdekawati (2016) and Julung et al, (2018). They reported that knowledge and the use of traditional medicines were obtained from personal experience, experiments and carried out from generation to generation.…”
Section: Discussionsupporting
confidence: 90%
“…The process of transferring the knowledge given by the predecessor to the successor should be given in stages and have the right steps so that the successor can absorb and implement that knowledge in daily life to treat disease. Julung, Supiandi, Ege, Mahanal, & Zubaidah (2018) said that the Dayak Desa community also inherited local knowledge about traditional medicine from generation to generation by believing that not all diseases could be cured medically. Lozada, Ladio, & Weigandt (2006) commonly, knowledge is transmitted vertically within a family, and it is also learned through practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The utilization of potentially medicinal plants by Dayak Desa community encountered various problems as follows: (i) only a few parents deliver the information about the types of medicinal plants and techniques of their use to their children (Julung et al 2018); (ii) modern medicine or western health treatments are gradually taking out traditional medicine (Kustiawan 2007); and (iii) forest degradation in West Kalimantan increases every year due to the increasing land clearance for the development of industrial forest plantations, oil palm plantations, illegal logging and shifting cultivation threatening the conservation of germplasm, and endemic species, especially plants that have potential as medicinal plants (Setyawan 2010). In addition, knowledge about the use of medicinal plants starts to vanish because it is only passed from generation to generation orally and has remained unwritten (Kaido et al 1997).…”
Section: Introductionmentioning
confidence: 99%